REKAYASA MATERIAL AKUSTIK RUANG DALAM DESAIN BANGUNAN Studi Kasus: Rumah Tinggal Sekitar Bandara Adisutjipto Yogyakarta - , KAHARUDDIN, S.PD.T; , Dr. Ir. H. Arif Kusumawanto, MT ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aims of the this research is determining the conditions and manipulate the acoustic material by the method of mathematical experiment. The focus of this research, namely the analysis of noise reduction and sound absorption of acoustical materials used in homes around the airport of Yogyakarta Adisutjipto then proceed with the analysis of sound absorption and noise reduction materials of engineering acoustics palm on the basis of buildingâs theoretical physics. The results of this research is that low sound absorption and noise reduction acoustic material present in the sample chamber is due to the nature of the material used has a sound reflector, so as to optimize noise reduction, an additional layer of acoustic material is needed to be used in the field. While the high sound absorption and noise reduction engineering materials because these materials are coconut fibers have a sound-absorbing properties. To further optimize the noise reduction to the addition of coconut fibers layer of acoustic material. In addition, the coconut fibers acoustical material can be used as an alternative sound dampening material at high frequencies that could potentially reduce the waste of nature.